High Times: The Effect of Medical Marijuana Laws on Student Time Use - Yu-Wei Luke Chu; Seth Gershenson (Institute for the Study of Labor (IZA), 2016)
Twenty-three states and the District of Columbia have passed medical marijuana laws. Previous research shows that these laws increase marijuana use among adults. In this paper, we estimate the effects of medical marijuana laws (MML) on secondary and post-secondary students' time use using time diaries from the American Time Use Survey. We apply a difference-in-differences research design and estimate flexible fixed effects models that condition on state fixed effects and state-specific time trends. We find that on average, part-time college students in MML states spend 42 fewer minutes on homework, 37 fewer minutes attending class, and 60 more minutes watching television than their counterparts in non-MML states. However, we find no effects of MMLs on secondary or full-time college students. These results provide evidence on the mechanisms through which marijuana use affects educational outcomes, young peoples' behavioral responses to MMLs (and reduced costs of obtaining marijuana), and that the impact of MMLs on student outcomes are heterogeneous and stronger among disadvantaged students.
Keywords: I18; K32; K42; 330; time use; medical marijuana; unintended consequences